Variations in the Left Coronary Artery (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background : There is a large spectrum of variations in the disposition of coronary arteries. Many of these variations are 'normal' and not considered as 'anomalous'1. These variations mainly occur in the Left Coronary Artery (LCA)2. While some of these are benign and have no clinical consequences, other variants can cause important clinical manifestations including sudden death of the individual3. Lack of knowledge of such variations can pose difficulties in percuteneous coronary arteriography, coronary artery bypass surgery or prosthetic valve replacement. A cadaveric study in unsuspected population can help to understand the variations that will be useful to determine the prevalence of certain variations. Thus the objective of this study was to analyze the characteristics of LCA that may be used in the diagnosis and treatment of its pathologies.Methods: The study was carried out in the Department of Anatomy, Chittagong Medical College (CMC) Chittagong over a period between Jan 2012 to Dec 2013 with ethical clearance. A detailed dissection of LCA and its branches in 50 cadaveric human hearts, fixed in 10% formalin was carried out to study normal and variant anatomy of LCA. The length of the main stem of LCA was measured by slide calipers.Results: The LCA was found to arise from the Left Posterior Aortic Sinus (LPAS) of the ascending aorta in 100% cases. The level of the ostia (Opening of coronary artery) was above the free margin of the aortic cusps in 98% cases. In all samples ostia were present below sinutubular ridge (A slight circumferential thickening separating bulbar aortic sinus and proximal ascending aorta). The length of the main stem of LCA (From origin to the point of termination into main branches) was found to range from 0.5-2 cm. The LCA showed bifurcation in 74%, trifurcation in 26% of cases. Left Anterior Descending artery (LAD) was found to terminate at the apex of the heart in 68% and at the posterior interventricular groove in 32% cases. The Left Circumflex artery (LCx) was terminated at the crux of the heart in 52%, near the crux in 44% and by crossing the crux in 4% cases. The Left Marginal Artery (LMA) which was present only in 34% cases, found to terminate nearer to the apex of the heart. 0% Left dominance of heart was observed.Conclusion: Simple attention to potential variations in the origin, number, level of ostia, length of the main stem, branching pattern, termination and distribution of LCA can greatly enhance clinical outcomes.Chatt Maa Shi Hosp Med Coll J; Vol.16 (1); Jan 2017; Page 42-47